Determination of the strength of polymer-metal interfaces under mixed mode loading using butt-bonded hollow cylinders. (March 2019) - Saborowski, Erik; Kießling, Robert; Dittes, Axel; Paczkowski, Gerd; Ihlemann, Jörn; Lampke, Thomas
Abstract: This contribution deals with the investigation of a novel testing approach for identifying the strength of polymer-metal interfaces under shear, tensile and combined shear-tensile load. To this end, a specimen geometry, being deployable independent on the material pairing, is determined by a simulative parameter study. Within the according finite element simulations, the cohesive zone approach is applied for the interface and a user-defined material model for the polymer. The simulation results are validated from an aluminum/polyamide 6 hybrid manufactured by hot pressing. Here, a NiAl5 thermal spray layer is utilized as mechanical adhesion promoter. The numerical as well as the experimental results prove that the identified geometry is well suited to determine the strength of polymer-metal interfaces. Furthermore, the experimental results reveal that the quadratic stress damage initiation criterion for the cohesive zone model is not appropriate for the investigated interface. Consequently, an alternative damage initiation criterion is proposed.